2020
DOI: 10.1021/acsami.9b21727
|View full text |Cite
|
Sign up to set email alerts
|

Realizing an Omega-Shaped Gate MoS2 Field-Effect Transistor Based on a SiO2/MoS2 Core–Shell Heterostructure

Abstract: Substantial progress has been made in the experimental synthesis of large-area two-dimensional transition metal dichalcogenide (TMD) thin films in recent years. This has provided a solid basis to build non-planar structures to implement the unique electrical and mechanical properties of TMDs in various nanoelectronic and mechano-electric devices, which, however, has not yet been fully explored. In this work, we demonstrate the fabrication and characterization of MoS2 field-effect transistors (FETs) with an ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…2020 [196] MoCl 5 + S(SiMe 3 ) 2 375 (800, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */GaN 8 ML 3.5 (2-4) n 10 2 2019 [197] 300 (900, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */sapphire 5 ML ≈3 (2.3-3.2) n ≈10 3 2019 [198] 350 (900, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */sapphire 4 ML 0.56 d) 6.4 (≈3-10) e) n n >10 6 10 3 2020 [202] 400 (900, S) 2020 [199] 375 (800, inert) (+ 400, CS 2 ) 2017 [118] Mo 2017 [281] 155 (400, Ar + 500, S + 900, S) 2017 [241] 150 ( 2019 [242] 150 ( 2020 [70] Sn(dmamp) 2 + H 2 S plasma 150…”
Section: Field-effect Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020 [196] MoCl 5 + S(SiMe 3 ) 2 375 (800, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */GaN 8 ML 3.5 (2-4) n 10 2 2019 [197] 300 (900, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */sapphire 5 ML ≈3 (2.3-3.2) n ≈10 3 2019 [198] 350 (900, S) (t)Au/Cr/Al 2 O 3 */MoS 2 */sapphire 4 ML 0.56 d) 6.4 (≈3-10) e) n n >10 6 10 3 2020 [202] 400 (900, S) 2020 [199] 375 (800, inert) (+ 400, CS 2 ) 2017 [118] Mo 2017 [281] 155 (400, Ar + 500, S + 900, S) 2017 [241] 150 ( 2019 [242] 150 ( 2020 [70] Sn(dmamp) 2 + H 2 S plasma 150…”
Section: Field-effect Transistorsmentioning
confidence: 99%
“…Using the same ALD process, Zhao et al. [ 199 ] deposited 5 nm thick MoS 2 films on SiO 2 of both planar and nanowire morphology. Top‐gate transistors constructed on both substrates had comparable yet modest performance (mobility 0.01–0.02 cm 2 V −1 s −1 and I on / I off ratio of ≈4 × 10 2 ), which is much lower compared to the aforementioned FETs on sapphire and GaN.…”
Section: Applications Of Atomic Layer Deposited 2d Metal Dichalcogenidesmentioning
confidence: 99%
“…This result is compared with our previously published results in Figure S6 (Supporting Information). Based on the same ALD-MoS 2 process, our previous study mainly investigated the application of new structures of transistors and logic circuits that were based on MoS 2 films and focused only on sapphire and SiO 2 substrates. , However, the influence of the growth substrate on MoS 2 films during the ALD growth process has not been systematically explored. Therefore, we compared MoS 2 films that were grown on various substrates and found that a smoother substrate that matches the crystal lattice of the grown film is more conducive to the growth of MoS 2 with high mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The SiO 2 /MoS 2 core-shell heterostructure gates and channels have been integrated into an U-shape. 205 The geometry takes advantage of avoiding the wet transfer process and minimizing surface contamination. The on/off ratio of the as-fabricated device shows a comparable value of 0.02 cm 2 V À1 s À1 .…”
Section: Thin Lm Transistors (Tfts)mentioning
confidence: 99%